2020
DOI: 10.1073/pnas.1921245117
|View full text |Cite
|
Sign up to set email alerts
|

Ancient MAPK ERK7 is regulated by an unusual inhibitory scaffold required forToxoplasmaapical complex biogenesis

Abstract: Apicomplexan parasites use a specialized cilium structure called the apical complex to organize their secretory organelles and invasion machinery. The apical complex is integrally associated with both the parasite plasma membrane and an intermediate filament cytoskeleton called the inner-membrane complex (IMC). While the apical complex is essential to the parasitic lifestyle, little is known about the regulation of apical complex biogenesis. Here, we identify AC9 (apical cap protein 9), a largely intrinsically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 83 publications
4
76
0
Order By: Relevance
“…The Toxoplasma genome encodes three MAPKs. Two of these kinases have been characterized: TgMAPKL1 (TGME49_312570) prevents centrosome overduplication ( 3 ), and TgERK7 (TGME49_233010) is required for conoid biogenesis ( 22 , 24 ). The gene TGME49_207820 encodes the Toxoplasma ortholog of MAPK2, a MAPK that is specific to and conserved in all alveolates, suggesting a specialized function ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Toxoplasma genome encodes three MAPKs. Two of these kinases have been characterized: TgMAPKL1 (TGME49_312570) prevents centrosome overduplication ( 3 ), and TgERK7 (TGME49_233010) is required for conoid biogenesis ( 22 , 24 ). The gene TGME49_207820 encodes the Toxoplasma ortholog of MAPK2, a MAPK that is specific to and conserved in all alveolates, suggesting a specialized function ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, even in Toxoplasma the function of the conoid is relatively poorly understood. Most studies of individual protein elements have identified molecules required for its assembly and stability [29,[31][32][33][34][35]. But other studies have implicated roles in control processes, including activating motility and exocytosis, both of which are requirements for invasion as well as host egress events [24,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The other is that we still know relatively little of the molecular composition of the conoid that would allow the objective testing for the presence of a homologous structure [5]. The conspicuous ultrastructure of conoids such as those of coccidians draw attention to tubulin being a major element, however it is known that there are other conoid proteins responsible for its assembly, stability, and function during invasion [24,[28][29][30][31][32][33][34][35]. To test if a homologous conoid cell feature is present in Aconoidasida, but cryptic by traditional microscopy techniques, fuller knowledge of the molecules that characterise this feature in a 'classic' conoid model is needed.…”
Section: Introductionmentioning
confidence: 99%
“…SAS6 is a highly conserved and it is responsible for the cartwheel assembly, crucial for establishing centriole and basal body geometry. One of the homologs is found at the centrosome (TgSAS6) while the other one, named SAS6-Like (TgSAS6L), is located at the conoid, a structure proposed to have emerged from an ancestral MTOC whose original function was to nucleate flagella (Francia et al, 2012;de Leon et al, 2013;Back et al, 2020;O'Shaughnessy et al, 2020). Indeed, de Leon, and col., showed that a SAS6L homolog localizes to the basal body of the flagellated trypanosomatid, Trypanosoma brucei, leading them to propose that SAS6L could exhibit a similar localization in T. gondii (de Leon et al, 2013).…”
Section: Context Of Microgamete Formationmentioning
confidence: 99%